Edukasi Upaya Preventif Dan Represif Penggunaan Gadget Berlebihan Oleh Anak-Anak Pada Warga Cinangka, Depok - Nida Handayani; Dini Gandini Purbaningrum; Linda Astriani (Universitas Serang Raya, 2024)
Parenting in the digital era is a challenge for parents to be able to adapt so they can sort out the positive and negative influences of technological developments on their children. The use of gadgets by children causes various problems when parents lack understanding in parenting in the digital era. The aim of community service activities is to provide assistance to parents in RT 05, Cinangka-Depok Village. The activity method is through: 1) education and socialization and assistance in using gadgets; 2) socialization of the application and child-friendly features; 3) parenting assistance in the digital era. Community service activities will be carried out in August and September 2023. The results of the activities obtained from the pretest and posttest calculations are as follows: a) knowing the negative impact of gadgets previously 67% increased to 92%; b) knowing the positive impact of gadgets, previously 56% to 87%; c) knowing the difference in the influence of gadgets on early childhood and adolescence, previously 58% increased to 93%; d) knowing child-friendly gadget applications and features, previously 43% increased to 89%; d) knowing about parenting in the digital era previously 52% increased to 91%. There has been an increase in the knowledge of participants in community service.